PRRT2 Related Epilepsies: A Gene Review - Massimino, Carmela Rita; Portale, Laura; Sapuppo, Annamaria; Pizzo, Francesco; Sciuto, Laura; Romano, Catia; Salafia, Stefania; Falsaperla, Raffaele (Journal of Pediatric Neurology, 2021)
PRRT2 encodes for proline-rich transmembrane protein 2 involved in synaptic vesicle fusion and presynaptic neurotransmitter release. Mutations in human PRRT2 have been related to paroxysmal kinesigenic dyskinesia (PKD), infantile convulsions with choreoathetosis, benign familial infantile epilepsies, and hemiplegic migraine. PRRT2 mutations cause neuronal hyperexcitability, which could be related to basal ganglia or cortical circuits dysfunction, leading to paroxysmal disorders. PRRT2 is expressed in the cerebral cortex, basal ganglia, and cerebellum. Approximately, 90% of pathogenic variants are inherited and 10% are de novo. Paroxysmal attacks in PKD are characterized by dystonia, choreoathetosis, and ballismus. In the benign familial infantile epilepsy (BFIE), seizures are usually focal with or without generalization, usually begin between 3 and 12 months of age and remit by 2 years of age. In 30% of cases of PRRT2-associated PKD, there is an association with BFIE, and this entity is referred to as PKD with infantile convulsions (PKD/IC). PRRT2 mutations are the cause of benign family childhood epilepsy and PKD/IC. On the other hand, PRRT2 mutations do not seem to correlate with other types of epilepsy. The increasing incidence of hemiplegic migraine in families with PRRT2-associated PKD or PKD/IC suggests a common disease pathway, and it is possible to assert that BFIE, paroxysmal kinesigenic dyskinesia, and PKD with IC belong to a continuous disease spectrum of PRRT2-associated diseases.
Keywords: PRRT2; movement disorders; benign familial infantile epilepsy; paroxysmal dyskinesia